Potential Mimicry of Viral and Pancreatic β Cell Antigens Through Non-Spliced and cis-Spliced Zwitter Epitope Candidates in Type 1 Diabetes - Mishto, Michele; Mansurkhodzhaev, Artem; Rodriguez-Calvo, Teresa; Liepe, Juliane (Frontiers in Immunology, 2021)
Increasing evidence suggests that post-translational peptide splicing can play a role in the immune response under pathological conditions. This seems to be particularly relevant in Type 1 Diabetes (T1D) since post-translationally spliced epitopes derived from T1D-associated antigens have been identified among those peptides bound to Human Leucocyte Antigen (HLA) class I and II complexes. Their immunogenicity has been confirmed through CD4+ and CD8+ T cell-mediated responses in T1D patients. Spliced peptides theoretically have a large sequence variability. This might increase the frequency of viral-human zwitter peptides, i.e. peptides that share a complete sequence homology irrespective of whether they originate from human or viral antigens, thereby impinging upon the discrimination between self and non-self antigens by T cells. This might increase the risk of autoimmune responses triggered by viral infections. Since enteroviruses and other viral infections have historically been associated with T1D, we investigated whether cis-spliced peptides derived from selected viruses might be able to trigger CD8+ T cell-mediated autoimmunity. We computed in silico viral-human non-spliced and cis-spliced zwitter epitope candidates, and prioritized peptide candidates based on: (i) their binding affinity to HLA class I complexes, (ii) human pancreatic  cell and medullary thymic epithelial cell (mTEC) antigens’ mRNA expression, (iii) antigen association with T1D, and (iv) potential hotspot regions in those antigens. Neglecting potential T cell receptor (TCR) degeneracy, no viral-human zwitter non-spliced peptide was found to be an optimal candidate to trigger a virus-induced CD8+ T cell response against human pancreatic  cell. Conversely, we identified some zwitter peptide candidates, which may be produced by proteasome-catalyzed peptide splicing, and might increase the likelihood of pancreatic  cells recognition by virus-specific CD8+ T cell clones, therefore promoting  cell destruction in the context of viral infections.